Content analysis of Islamic religious education student textbooks and morals for class VIII Islamic junior high school published by the ministry of education and culture revised edition 2017 - Hidayat, Ilman; Nurkhamidi, Aris; Yuniati, Mei (IAIN Salatiga, 2022)
In an educational process, the use of books is one of the most important elements. Without books, learning becomes unbalanced because there is no reliable reference source. This study focuses on finding out whether the textbook for Islamic Religious Education and Morals for Class VII SMP/MTs is appropriate in terms of content or material content. The type of approach used in this study is a library research approach through the documentation method with the analysis technique being content analysis. Data analysis was carried out systematically and logically starting from reading and analyzing all the data. The results of this study indicate that first, the contents of the textbook material for Islamic Religious Education and Morals for Class VIII SMP/MTs students in terms of the four sub-components of the content feasibility assessment are also suitable for use with details of the percentage of eligibility, namely 100% for the SK and KD conformity sub-components, the development and needs of students, 94.6% for scientific substance and life skills, 87.5% obtained by the insight sub-component to advance and develop and 82.1% for the diversity of social values. Second, the contents of the textbook material for students of Islamic Religious Education and Morals for Class VII SMP/MTs when viewed from the four dimensions, namely the spiritual, social, knowledge and skill dimensions are appropriate for use. The details of the percentage of eligibility obtained are 100% for the spiritual dimension, 100% for the social dimension, 92.90% for the knowledge dimension and 89.90% for the skills dimension. The results of this data analysis can be concluded that the two categories above, namely the four-dimensional elements and four sub-components of content feasibility, have been accurate to be used in assessing the feasibility of the content of textbooks.